UGT85A84 Catalyzes the Glycosylation of Aromatic Monoterpenes in Osmanthus fragrans Lour. Flowers - Zheng, Riru; Zhu, Zhenyin; Wang, Yanli; Hu, Shiyang; Xi, Wan; Xiao, Wei; Qu, Xiaolu; Zhong, Linlin; Fu, Qiang; Wang, Caiyun (Frontiers in Plant Science, 2019)
The monoterpenes linalool and its oxides are the key aroma-active compounds in Osmanthus fragrans Lour. flowers. The glycosides of these monoterpenes accumulate throughout flowering, leading to considerable storage of potential aroma constituents which account for a majority of non-volatile aroma compounds. However, the UDP-glycosyltransferase (UGT) responsible for the glycosylation of linalool and its oxides has not been clarified. Four candidate OfUGTs (UGT85A82, UGT85A83, UGT85AF3 and UGT85A84) with high homology to the known terpenoid UGTs were screened by transcriptome sequencing. Over-expression of the candidate OfUGTs in tobacco showed that UGT85A84 glycosylated linalool oxides in planta. Since the transcript levels of UGT85A84 were positively correlated with glycoside accumulation, recombinant UGT85A84 protein was subjected to reactions with aglycones and sugar donors. Two formate adducts were exclusively detected in UDP-Glc with linalool and linalool oxide reactions by liquid chromatography-mass spectrometry (LC-MS), indicating that UDP-Glc was the specific sugar donor. The kinetic parameters demonstrated that UGT85A84 both glycosylated linalool and lianlool oxides in vitro. Further analysis demonstrated that the transcription levels of MEP pathway genes might play an important role in mediating terpenoid glycosylation. Our findings unraveled the mechanism underlying the glycosylation of essential aroma compounds in flowers. This study will facilitate the application of potential aroma contributors in future industries.